Graphene: recent advances in engineering, medical and biological sciences, and future prospective - Fatemeh Emadi; Abbas Amini; Younes Ghasemi; Ahmad Gholami (Shiraz University of Medical Sciences, 2018)
Graphene, a two dimensional carbon allotrope, has been appeared as an interesting material of the 21st century, and received world-wide attention due to its extraordinary thermal, optical, and mechanical properties. Graphene and its derivatives are being studied in different field of science from medicine and pharmaceutics to engineering and industries. Graphene materials have mainly been explored in electronics, clean energy devices, biosensors and environmental remediation also in biomedicine field, their antimicrobial activity and their capacity as drug delivery or gene delivery platforms and tissue engineering scaffold have been reported. This article provides an overview of graphene and its recent advances in different fields including biomedicine and industries.